NARKOBA, MINUMAN BERALKOHOL DAN PENGARUHNYA BAGI PERKEMBANGAN SISWA DI PERUMAHAN ORGANDA PADANG BULAN - Kristina Sawen; Dahliana Ketaren (JURNAL PENGABDIAN PAPUA, 2020)
Narcotics and alcoholic beverages are a means used to destroy common sense, morals, and morals that have the potential to damage one's personality. Because the working system of this type attacks a person's nerves when consumed. Even so, but the positive benefits for the development of human life in the medical field, so that its existence is permitted but in certain procedures and rules. The result is that it is very detrimental to attack everyone so that uses other than medical interests based on certain permits and procedures are strictly prohibited. Especially when circulating within the children. In fact and fact, still groups of children fall into the life of drugs and alcoholic beverages, so that it will have fatal consequences for the children themselves and for the life of the nation in the future. So it is important to be socialized regularly at every opportunity to help remind children to avoid drugs and alcoholic beverages.Keywords: Narcotics, alcoholic beverages, children